2018
DOI: 10.1111/ajt.14565
|View full text |Cite
|
Sign up to set email alerts
|

T cell–mediated rejection is a major determinant of inflammation in scarred areas in kidney allografts

Abstract: Inflammation in fibrosis areas (i-IF/TA) of kidney allografts is associated with allograft loss; however, its diagnostic significance remains to be determined. We investigated the clinicohistologic phenotype and determinants of i-IF/TA in a prospective cohort of 1539 kidney recipients undergoing evaluation of i-IF/TA and tubulitis in atrophic tubules (t-IF/TA) on protocol allograft biopsies performed at 1 year posttransplantation. We considered donor, recipient, and transplant characteristics, immunosuppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 34 publications
6
84
1
2
Order By: Relevance
“…observations have been confirmed in 2 recent studies, 15,16 and recently, inflammation in areas of atrophy/fibrosis has been incorporated into the latest Banff scoring, using the terminology "i-ifta". 17 At the initiation of the DeKAF study, the single-bead method for DSA determination was just becoming widely used.…”
Section: Thesementioning
confidence: 74%
See 1 more Smart Citation
“…observations have been confirmed in 2 recent studies, 15,16 and recently, inflammation in areas of atrophy/fibrosis has been incorporated into the latest Banff scoring, using the terminology "i-ifta". 17 At the initiation of the DeKAF study, the single-bead method for DSA determination was just becoming widely used.…”
Section: Thesementioning
confidence: 74%
“…14 These observations have been confirmed in 2 recent studies, 15,16 and recently, inflammation in areas of atrophy/fibrosis has been incorporated into the latest Banff scoring, using the terminology "i-ifta". Mengel et al also showed that the total inflammation score (iatr plus inflammation in nonatrophic parenchyma [as routinely scored in Banff]) was associated with worse graft survival.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 81%
“…This theme is also advocated by another recent publication 2 and by the forthcoming Banff report, 3 contradicting the previous Banff consensus opinion that i-IFTA lesions are a reflection of injury and a risk for progression but not a sign of active TCMR. We write because molecular analyses do not support the conclusion that i-IFTA indicates chronic active TCMR.…”
Section: To the Editormentioning
confidence: 92%
“…The consensus decision to add this category and to base it in part, but only in part, on the presence of i-IFTA was based primarily on data from 3 studies [3][4][5] that together demonstrated the following:…”
Section: Comments On Famulski and Halloran Ajt I-ifta Lettermentioning
confidence: 99%